Diet of the Leopard Seal Hydrurga leptonyx at the Danco Coast, Antarctic Peninsula - Casaux, Ricardo Jorge; Baroni, A.; Ramón, A.; Carlini, A.; Bertolin, María Lila; Di Prinzio, Cecilia Yanina (Polar Biology)
A total of 14 scats of the Leopard Seal were collected on ice floes close to Cierva Point, Danco Coast, Antarctic Peninsula, during February and March 2000. Krill was the most frequent and numerous prey and also constituted the bulk of the diet; penguins and fish followed in importance by mass. Among fish, Gobionotothen gibberifrons was the most frequent prey and also predominated by mass whereas the myctophid Gymnoscopelus nicholsi was the most numerous prey. The results are compared with previous studies and the differences in the composition of the diet observed among the Leopard Seal and other seals at the study area are discussed. Fil: Casaux, Ricardo Jorge. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de la Patagonia "San Juan Bosco"; Argentina Fil: Baroni, A. Universidad de Buenos Aires. Facultad de Farmacia y Bioquímica; Argentina Fil: Ramón, A. Municipalidad de Esquel. Subsecretaría de Medioambiente; Argentina Fil: Carlini, A. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Bertolin, María Lila. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Di Prinzio, Cecilia Yanina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina